2021
DOI: 10.1038/s41598-021-03390-w
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular interactions between mast cells and stromal fibroblasts obtained from canine cutaneous mast cell tumours

Abstract: Mast cell tumours (MCTs) are the most frequent malignant skin neoplasm in dogs. Due to the difficulty in purifying large numbers of canine neoplastic mast cells, relatively little is known about their properties. A reproducible in vitro model is needed to increase the understanding about the phenotype and functional properties of neoplastic mast cells. In the present study, we describe the establishment of primary cocultures of neoplastic mast cells from canine cutaneous MCTs and cancer-associated fibroblasts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…More so, 3D systems allowing interactions between the tumor microenvironment and the corresponding neoplastic cells have proven essential in designing experimental approaches to personalized medicine and predicting the effect of different drugs also in dogs. [11,18,20] The study of speci c canine tumors is considered useful as they represent spontaneous models for the human counterparts. Compared to xenograft or genetically modi ed murine models, the dog shares with humans more than ~ 650 Mb of ancestral sequences; furthermore, canine DNA and protein sequences are more similar to humans compared to rodents.…”
Section: Introductionmentioning
confidence: 99%
“…More so, 3D systems allowing interactions between the tumor microenvironment and the corresponding neoplastic cells have proven essential in designing experimental approaches to personalized medicine and predicting the effect of different drugs also in dogs. [11,18,20] The study of speci c canine tumors is considered useful as they represent spontaneous models for the human counterparts. Compared to xenograft or genetically modi ed murine models, the dog shares with humans more than ~ 650 Mb of ancestral sequences; furthermore, canine DNA and protein sequences are more similar to humans compared to rodents.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated the better performances and the essential role of 3D culture systems for the understanding of treatment response and the emergence of chemo-resistant clones. More so, 3D systems allowing interactions between the tumor microenvironment and the corresponding neoplastic cells have proven essential in designing experimental approaches to personalized medicine and predicting the effect of different drugs also in dogs [ 11 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%